Involvement of hnRNP A1 in the matrix metalloprotease-3-dependent regulation of Rac1 pre-mRNA splicing - Pelisch, Federico Gaston (2012)
Rac1b is an alternatively spliced isoform of the small GTPase Rac1 that includes the 57-nucleotide exon 3b. Rac1b was originally identified through its over-expression in breast and colorectal cancer cells, and has subsequently been implicated as a key player in a number of different oncogenic signaling pathways, including tumorigenic transformation of mammary epithelial cells exposed to matrix metalloproteinase-3 (MMP-3). Although many of the cellular consequences of Rac1b activity have been recently described, the molecular mechanism by which MMP-3 treatment leads to Rac1b induction has not been defined. Here we use proteomic methods to identify heterogeneous nuclear ribonucleoprotein (hnRNP) A1 as a factor involved in Rac1 splicing regulation. We find that hnRNP A1 binds to Rac1 exon 3b in mouse mammary epithelial cells, repressing its inclusion into mature mRNA. We also find that exposure of cells to MMP-3 leads to release of hnRNP A1 from exon 3b and the consequent generation of Rac1b. Finally, we analyze normal breast tissue and breast cancer biopsies, and identify an inverse correlation between expression of hnRNP A1 and Rac1b, suggesting the existence of this regulatory axis in vivo. These results provide new insights on how extracellular signals regulate alternative splicing, contributing to cellular transformation and development of breast cancer.